A new synthetic application of (dichloroiodo)benzene in reactions with alkenes and alkynes; Korus 2004; Vol. 2 - Yusubova R. Ya. Roza Yavidovna; Filimonov V. D. Viktor Dmitrievich; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Ki Whan Chi (2004, 2004)
A convenient synthesis of vicinal methoxychlorides, methoxyiodides from alkenes and alkynes using PhICl2/CH3OH, I2/PhICl2/CH3OH is described.